Ghrelin Treatment Improves Lipid Metabolism and Hepatic Degeneration in Ovariectomized Rats - YEGEN, BERRAK; ÖZBEYLİ, DİLEK; ERCAN, FERİHA; KAYA, ÖZLEM TUĞÇE (GAZI UNIV, FAC MED, 2020)
Objective: Metabolic disorders occurring in post-menopausal period increase the risk for development of fatty liver disease in women. Aim of the study was to evaluate possible effects of ghrelin on metabolic biomarkers and hepatic morphology in ovariectomized (OVT) rats. Methods:Under ketamine-chlorpromazine anesthesia (100 mg/kg, 0.75 mg/kg), Sprague-Dawley rats (n=12) underwent bilateral OVT, while control group had sham-surgery (n=6). Four weeks after surgery, half of OVT rats were treated intraperitonally with ghrelin (1 mg/kg/hafta) for 4 weeks, while others were not treated. Rats were euthanized by cardiac puncture at the end of 8th weeks, and serum levels of glucose, insulin, aspartate aminotransferase (AST), high-density lipoprotein (HDL), low-density lipoprotein (LDL), very low-density lipoprotein (VLDL), triglycerides, estradiol and progesterone were measured by an automated analyzer. Results: Increased body weights in OVT rats (p<0.001) recorded at the end of 2 months was not changed with ghrelin. Serum estradiol and progesterone levels were reduced (p<0.05) verifying altered gonadal hormone status, but insulin and glucose levels were not changed. Reduced HDL and increased LDL levels (p<0.0.5) were evident in non-treated OVX rats, while ghrelin treatment depressed LDL levels (p<0.0.5), but did not change HDL levels. However, ghrelin in OVT rats depressed triglycerides, VLDL and AST levels significantly (p<0.05). Moderate sinusoidal congestion, activated Kupffer cells and hepatocytes with ballooning degeneration was observed in non-treated OVT rats, while significant improvements were present in livers of ghrelin-treated rats. Conclusion: In conclusion, mild dyslipidemia and hepatic degeneration in early post-menopausal period appear to be attenuated by ghrelin treatment, and require further investigation.
Keywords: Ghrelin; Postmenopausal; dyslipidemia; FATTY LIVER-DISEASE; ORGAN INJURY; GHS-R; OBESITY; DYSFUNCTION; PREVALENCE; RECEPTOR; RISK; EPIDEMIOLOGY; INFLAMMATION